2009
DOI: 10.1161/circep.108.818211
|View full text |Cite
|
Sign up to set email alerts
|

Remote Robotic Navigation and Electroanatomical Mapping for Ablation of Atrial Fibrillation

Abstract: Background-Radiofrequency current ablation of atrial fibrillation (AF) requires high technical skills to achieve optimal catheter stability and is associated with an individually high x-ray exposure to both the patient and the operator. To facilitate catheter navigation and to reduce the operator's x-ray burden, remote navigation (RN) systems have been developed. Considerations for navigation of a novel remote robotic navigation system in pulmonary vein isolation (PVI) procedures are reported. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 22 publications
(23 reference statements)
12
59
0
1
Order By: Relevance
“…Using robotic navigation may affect the risk for SCL for the following reasons: a larger sheath (14F) is advanced into the LA, 8 additional flushing of the inner and outer robotic sheath is required, 19,20 and the tip-to-tissue contact may be enhanced using robotic navigation, thereby potentially increasing the risk of charring, thrombus formation, or gaseous steam formation caused by tissue overheating. 13,15,16 Tissue overheating causing increased steam formation might be 1 of the major reasons why irrigated catheters still produce SCL as irrigation cools the catheter tip but not the tissue.…”
Section: Manually Performed Ablation Versus Rns-assisted Ablationmentioning
confidence: 99%
“…Using robotic navigation may affect the risk for SCL for the following reasons: a larger sheath (14F) is advanced into the LA, 8 additional flushing of the inner and outer robotic sheath is required, 19,20 and the tip-to-tissue contact may be enhanced using robotic navigation, thereby potentially increasing the risk of charring, thrombus formation, or gaseous steam formation caused by tissue overheating. 13,15,16 Tissue overheating causing increased steam formation might be 1 of the major reasons why irrigated catheters still produce SCL as irrigation cools the catheter tip but not the tissue.…”
Section: Manually Performed Ablation Versus Rns-assisted Ablationmentioning
confidence: 99%
“…6,15,16 This is of particular importance since interventional electrophysiologists accumulate a significant amount of radiation exposure throughout their professional careers.…”
Section: Radiation Exposure To the Operatormentioning
confidence: 99%
“…Special catheters with magnets affixed to their distal end can be navigated PV isolation reports in paroxysmal and persistent AF patients using the Sensei system have consistently shown significant shortening of the fluoroscopy time. [48][49][50][51][52] Remote isolation of the PV showed similar midterm follow-up (six-months to one-year) free of atrial arrhythmias to manual point-by-point radiofrequency delivery. Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 80%
“…Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias. [50][51][52] Initial reports using the Sensei system had raised the concern of higher rate of cardiac tamponade than conventional manual RF delivery 53 , which might be related to remote manipulation of the stiff steerable Artisan catheter (Hansen Medical, Mountain View, CA, US). Further experience and introduction of a special feature of the system to indirectly estimate catheter contact force on the tissue (IntelliSense) have shown that tamponade rates are not greater than the conventional manual approach and may be more related to different temperature and power RF settings.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 99%